2010
DOI: 10.1038/hr.2010.260
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolysis and insulin sensitivity in imidapril and candesartan (FISIC study) recipients with hypertension

Abstract: The aim of this study was to evaluate the effects of imidapril and candesartan on fibrinolysis and insulin sensitivity in normoweight hypertensive patients. After a 2-week wash-out period, 61 patients with mild-to-moderate hypertension were randomized to imidapril or candesartan for 12 weeks. Blood pressure (BP), plasma tissue plasminogen activator (t-PA) and plasminogen activator inhibitor-1 (PAI-1) antigen activities were evaluated at baseline and during treatment. The patients underwent a euglycemic-hyperin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…In addition, results of multiple intervention studies indicated that lifestyle modification 39,40 and pharmacologic treatment for hypertension, 41,42 such as the angiotensin converting enzyme inhibitor, imidapril or the angiotensin II type 1 receptor antagonist, irbesartan, not only reduced BP values but also improved insulin sensitivity and endothelial function. Therefore, weight management or drug therapy may be necessary for hypertensive patients to reduce incidence of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, results of multiple intervention studies indicated that lifestyle modification 39,40 and pharmacologic treatment for hypertension, 41,42 such as the angiotensin converting enzyme inhibitor, imidapril or the angiotensin II type 1 receptor antagonist, irbesartan, not only reduced BP values but also improved insulin sensitivity and endothelial function. Therefore, weight management or drug therapy may be necessary for hypertensive patients to reduce incidence of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…2,49,50 Although in the present study we did not evaluate changes in tPA levels, data from previous studies by ourselves and other authors indicated that ARB, which do not affect the metabolism of bradykinin, do not influence or even decrease plasma tPA. 1,25,28,29 Coronary release of tPA from the endothelium is an important defense against coronary heart disease. The recently published results of the Shiga Plasminogen Activator In Coronary Circulation study 51 have demonstrated that ACE inhibition increased coronary release of tPA, although only in women.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Accordingly, most, although not all, 23,24 direct comparative studies on the effects of ACE-Is and ARBs on the fibrinolytic balance observed a decrease in PAI-1 plasma levels with ACE-Is, but not with ARBs. [25][26][27][28][29] One possible reason for such a dissimilar effect might be the different effect of the two drug classes on plasma Ang II. Unlike ACE-Is, which inhibit ACE-dependent production of Ang II, thus decreasing its plasma levels, treatment with ARBs is known to elevate markedly circulating Ang II.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In a homogenous population of normoweight (BMIo25 kgm À2 ) hypertensive patients, the effects of ARB on fibrinolysis and insulin sensitivity in comparison with the effects of ACE-I have not yet been determined. Fogari et al 8 compared the effects of 12-week treatment with the ACE-I imidapril and the ARB candesartan on plasma PAI-1 antigen and its activity, and on plasma t-PA activity in normoweight hypertensive patients. In this study, despite similar blood pressure reduction, imidapril but not candesartan improved the fibrinolytic balance, possibly through bradykinin-mediated effects on insulin sensitivity and endothelial function.…”
mentioning
confidence: 99%